A One-Year Retrospective Radiographic Assessment of Marginal Bone Loss Around Basal Implants and Impact of Multiple Risk Factors using Multivariate Analysis - Yahya Abdali; Universidad de Concepción School of DentistryDepartment of Oral and Maxillofacial Surgery, College of Dentistry, Misan University, Misan, Iraq; Mustafa Al-Mash'hadani; Firas SO Albaaj (Universidad de Concepción., 2021)
Background: Factors like medical and periodontal conditions, implant location and smoking can affect marginal bone loss (MBL) of basal implants. Objectives: The purpose of this study is to explore the association of MBL with multiple variables including gender, age, smoking status, diabetes, implant placement protocol, location of implant, and type of prosthesis. Material and Methods: A total of 156 single-piece basal implants (Dr. Ihde Dental AG in Gommiswald, Switzerland) were placed in 44 patients. Dental panoramic tomographs were obtained postoperatively and following a one-year of service to determine MBL on mesial and distal sides. The association of MBL with the multiple variables was analysed using the multivariate and the random forest analysis. Results: The mean mesial and distal MBL was 0.64 millimetres. None of the implants presented MBL exceeding 1 millimetre. All implants were retained without complications during the first year of service. The MBL was remarkably associated with the smoking status, diabetes, location of implant and implant placement protocol. Diabetes mellitus is the most vital parameter in predicting MBL. Conclusion: The mean MBL of all implants did not exceed the threshold of 1 millimetre during the first year of service. When placing implants in patients who smoke and have diabetes, care should be taken.